2020
DOI: 10.1123/pes.2019-0126
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Structured Physical Activity on Inflammation and Immune Activation Profile of Antiretroviral Therapy-Experienced Children Living With HIV

Abstract: Aim: To compare the markers of inflammation and immune activation in virally suppressed HIV-infected children on antiretroviral therapy, who practiced regular structured exercise comprising running and yoga to those who did not over a 2-year period. Methods: This retrospective cohort study included 72 children aged 8 to 16 years divided into 2 groups, exercisers (n = 36) and the nonexercisers (n = 36) based on their intentional physical activity. The analyses were carried out at baseline and after 2 years (Y2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Figure 1 illustrates the PRISMA 2020 flow diagram for the selection process of the studies: a total of 1,473 articles were included from the three databases, and after removing the duplicates and non-eligible studies, 15 articles remained eligible for this review (6 cross-sectional articles, 5 studies reported the acute effects of physical activity, and 5 articles showed the chronic effects of physical activity). The sample size ranged from 12 to 369 participants (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). The age of participants ranged from 9 to 18 years old (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 illustrates the PRISMA 2020 flow diagram for the selection process of the studies: a total of 1,473 articles were included from the three databases, and after removing the duplicates and non-eligible studies, 15 articles remained eligible for this review (6 cross-sectional articles, 5 studies reported the acute effects of physical activity, and 5 articles showed the chronic effects of physical activity). The sample size ranged from 12 to 369 participants (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). The age of participants ranged from 9 to 18 years old (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Resultsmentioning
confidence: 99%
“…The sample size ranged from 12 to 369 participants (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). The age of participants ranged from 9 to 18 years old (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Thirteen studies used blood samples (27,(29)(30)(31)(32)(34)(35)(36)(37)(38)(39)(40) while 2 saliva (33) and buccal swabs (28) respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although “no evidence of effect” could be sustained, a systematic review including 23 clinical trials and 1073 participants [ 14 ] could not find an association between beneficial effects and biomarker improvements after ≥4 weeks of aerobic or/and resistance exercise. A longer-term study carried out retrospectively in children with HIV who practiced exercise regularly for 2 years showed reduced levels of immune activation markers such as sCD14, TNF-α, interferon-gamma (IFN-γ), and IL-10, and lower expression of CD38 on CD4 + T cells [ 26 ]. This latter result is in concordance with the reduction on activation markers expressed in CD4 + and CD8 + T cells and NK cells in patients with higher physical activity from our series.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore important to continue to monitor the growth and endurance levels of all children as they go through adolescence as the impairments experienced by children may change. High levels of MVPA and aerobic fitness may also have additional benefits in CLHIV, such as the prevention of cardiovascular risk factors commonly experienced (De Lima et al 2019 ) or improving inflammatory profiles (Gopalan et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%